An AMOLED AC-Biased Pixel Design Compensating the Threshold Voltage and I-R Drop - Ching-Lin Fan; Hui-Lung Lai; Yan-Wei Liu (International Journal of Photoenergy)
We propose a novel pixel design and an AC bias driving method for active-matrix organic light-emitting diode (AM-OLED) displays using low-temperature polycrystalline silicon thin-film transistors (LTPS-TFTs). The proposed threshold voltage and I-R drop compensation circuit, which comprised three transistors and one capacitor, have been verified to supply uniform output current by simulation work using the Automatic Integrated Circuit Modeling Simulation Program with Integrated Circuit Emphasis (AIM-SPICE) simulator. The simulated results demonstrate excellent properties such as low error rate of OLED anode voltage variation (<0.7%) and low voltage drop of VDD power line. The proposed pixel circuit effectively enables threshold-voltage-deviation correction of driving TFT and compensates for the voltage drop of VDD power line using AC bias on OLED cathode.